2014
DOI: 10.1111/pce.12336
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic volatile organic compound emissions from vegetation fires

Abstract: The aim of this paper was to provide an overview of the current state of the art on research into the emission of biogenic volatile organic compounds (BVOCs) from vegetation fires. Significant amounts of VOCs are emitted from vegetation fires, including several reactive compounds, the majority belonging to the isoprenoid family, which rapidly disappear in the plume to yield pollutants such as secondary organic aerosol and ozone. This makes determination of fire-induced BVOC emission difficult, particularly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 80 publications
(118 reference statements)
5
66
1
2
Order By: Relevance
“…In contrast, we observed above the PBL (> 1,2000 m) an impressive increase of about 60% of the isoprene in AP (2.4 ppbv) relative to the BG value (1.5 ppbv), which is about the same mean value found in FP (1.6 ppbv). These high levels of isoprene at higher altitudes in air masses 305 affected by biomass burning emissions are likely to be associated with the heat released from vegetation fires affecting nearby plants with enough energy to release significant amounts of isoprene to the atmosphere, especially in tropical forest fires in Brazil (Ciccioli et al, 2014). Müller et al (2016), for example, found isoprene mixing ratios up to 15 ppbv in a smoke plume from a small forest fire in Georgia, USA.…”
Section: Isoprene and Its Oxidation Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we observed above the PBL (> 1,2000 m) an impressive increase of about 60% of the isoprene in AP (2.4 ppbv) relative to the BG value (1.5 ppbv), which is about the same mean value found in FP (1.6 ppbv). These high levels of isoprene at higher altitudes in air masses 305 affected by biomass burning emissions are likely to be associated with the heat released from vegetation fires affecting nearby plants with enough energy to release significant amounts of isoprene to the atmosphere, especially in tropical forest fires in Brazil (Ciccioli et al, 2014). Müller et al (2016), for example, found isoprene mixing ratios up to 15 ppbv in a smoke plume from a small forest fire in Georgia, USA.…”
Section: Isoprene and Its Oxidation Ratiomentioning
confidence: 99%
“…Chem absorbed by plants with low boiling point (e.g., Tisoprene  307 K), macromolecular bonds can be broken (i.e., low-temperature pyrolysis), gasification reactions converting carbon in the solid char to CO and CO2 can occur and the flames efficiently oxidize the volatile gases to species such as H2O, CO2, and NOx (Bertschi et al, 2003;Longo et al, 2009). The release of isoprene and other BVOCs is dependent on the different phases of biomass combustion, and diverse vegetation communities affect the amount and diversity of volatile organic compounds released (Ciccioli et al, 2014). In this disturbed atmosphere, the assumed natural 105 efficient OH recycling mechanism is affected, altering the oxidative capacity of the atmosphere.…”
mentioning
confidence: 99%
“…BVOCs affect atmospheric composition and climate via ozone production, lengthening the lifetime of atmospheric methane, and contributing to secondary organic aerosol formation (Penuelas and Staudt, 2010;Wu et al, 2012). BVOC emission factors might also be drastically influenced by wildfires (Ciccioli et al, 2014), which in turn are driven by species composition and vegetation density. Thus, different successional trajectories of ecosystem structure and composition recovery have the potential to directly modify air quality and climatic conditions under which regrowth occurs, potentially creating positive or negative climate system feedbacks.…”
Section: Comparison To Observations and Previous Studiesmentioning
confidence: 99%
“…If open-air burning is used as a pruning disposal method, the annual potential yield of jatropha prunings of 8.72 Mg·ha −1 [25,26] on a ten-year cycle emits about 13 Mg CO 2 ha −1 per year (considering an average emission of 1550 g CO 2 kg −1 of dry matter burned [67]). On the contrary, the same amount of woody biomass could provide 134 GJ·ha −1 per year (considering a jatropha pruning LHV of 15.44 MJ·kg dm −1 ).…”
Section: Discussionmentioning
confidence: 99%